Parámetros estadísticos para determinar el crecimiento de una plantación de la especie Simarouba amara Aubl, del Centro de Investigación Forestal CIEFOR - Puerto Almendra - UNAP, Iquitos - Loreto - 2021 - Borbor Villanueva, Frank Salomón (2022)
This research work was carried out in a 39-year-old plantation of the Simarouba amara aubl, (marupa) of the CIEFOR Forest Research Center – Puerto Almendra – UNAP. The research type is non-experimental considering that it is a qualitative research. According to the obtained results, it ca be indicated that the Annual Current Increase for the marupa species was 10,25 cm on average for the 41 trees, the Average Annual Increase for the marupa species was 0,86 cm on average for the 41 trees,the Annual Periodic Increase for the marupa species was 2,01 cm on average for the 41 trees. The research hypothesis is confirmed by knowing the statistical parameters it is possible to determine the growth of the trees.